One size does (obviously not) fit all: Using product attributes for wine market segmentation - Eugenio Pomarici; Marco Lerro; Polymeros Chrysochou; Riccardo Vecchio; Athanasios Krystallis (Wine Economics and Policy, 2017)
The intense competition affecting the wine industry in recent decades has forced wineries and retailers to reshape their marketing strategies on the basis of consumer preferences. The current study aims to identify such preferences and the effects they might have in influencing consumer decisions. Preferences for different wine attributes as well as the psychographic traits of respondents were revealed through a web-based questionnaire administered to 504 wine consumers living in the wider metropolitan area of New York. Best-worst scaling (BWS) was used to detect consumer preferences for eleven wine attributes. Based on individual best-worst scores, a latent class segmentation analysis was implemented to classify consumers into four segments on the basis of psychographic characteristics such as involvement, subjective knowledge, innovativeness and loyalty proneness. The four segments identified (i.e. experientials, connoisseurs, risk minimizers and price-sensitive) differ significantly in terms of their preferences towards wine and psychographic characteristics, suggesting that a mass marketing approach is no longer suitable. Accordingly, managers need to adapt their marketing strategies to meet the preferences of different target groups. The results provide broad implications for marketers, wineries and retailers interested in successfully targeting consumers in a highly competitive market.
Keywords: 330; Best-worst scaling; Consumer preferences; US wine consumers